Co-Infection Rates between SARS-CoV-2 and RSV in Oropharyngeal, Nasopharyngeal Aspirate and Saliva Samples of COVID-19 Patients, Shiraz, South of Iran - Jannan Ghapanchi; Ali Dehghani Nazhvani; Fahimeh Rezazadeh; MItra Farzin; Afagh Moatari; Sina Masoudi; Mohamad Reza Kalantari; Reza Derafshi; Hossein Sedarat (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Determining the prevalence of respiratory viruses' coinfection with coronavirus disease 2019 (COVID-19) is essential to defining its true clinical influence.Purpose: This study aimed to evaluate co-infection rates between severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) and respiratory syncytial virus (RSV) in infected patients in Shiraz, south of Iran.Materials and Method: In a cross-sectional descriptive study, oropharyngeal, nasopharyngeal aspirate (NPA), and saliva samples of 50 COVID-19 patients who were referred to Ali-Asghar hospital (Shiraz, Iran) from March to August 2020, were collected. A control group consisted of age and sex-matched healthy participants. The nasopharyngeal and oropharyngeal aspirates were collected by sterile swabs. All cases were hospitalized, and all SARS-CoV-2 patients had a fever and respiratory symptoms. The samples were packed in a vial with 1 mL of transport medium and transported to the Valfagre specialty laboratory, where they were tested for RSV using a real-time polymerase chain reaction (PCR).Results: 100 nasopharyngeal/oropharyngeal aspirates and saliva samples including 50 healthy controls (24 females, 26 males) and 50 COVID-19 patients' samples (27 males and 23 females) were studied. There was no significant difference regarding age as well as gender between both groups (P>0.05). None of the healthy subjects was infected with RSV; however, 5(10%) patients from COVID-19 group were infected with the RSV virus. Chi-square test did not show a significant difference between RSV infection in COVID-19 patients and healthy subjects.Conclusion: The outcome of present research showed that concurrent RSV with COVID 19 infection might be seen in hospitalized patients in Shiraz Southwest of Iran. For more reliable findings, further research on bigger populations, including more pathogens in several places around the country, and considering the severity of symptoms is required.